Thelonious Mouse - Protopopescu, Orel Odinov (Farrar Straus Giroux, 2011)
Thelonious is a hipster mouse who cannot keep himself from taunting the cat of the house, but once Thelonious discovers a toy piano, he and the cat make some beautiful music together.